Large Isolated Nasoorbital Type of Frontoethmoidal Encephalomeningocele: A Case Report With Long-Term Follow-up. Issue 1 (July 2022) - Charoenvicha, Chirakan; Khwanngern, Krit; Sirimaharaj, Wimon
Abstract: Frontoethmoidal encephalomeningocele (FEEM) is a rare congenital craniofacial malformation with increased incidence in Southeast Asia, especially in Thailand. Because of its rarity, main treatment obstacles include the lack of surgical treatment techniques and long-term postoperative follow-up data. The authors present the case of a 9-month-old boy who was born with a large isolated nasoorbital type of FEEM, which had a pressure effect on his right eye, nose, and facial complex. Preoperative computed tomography of the facial bone was performed to evaluate the external bony defect. This study aims to present surgical correction of FEEM with Chula's technique and long-term 7-year postoperative follow-up including both clinical and imaging aspects.